Urban form centrality and thermal environment: An empirical study of Chinese megacities. (August 2022) - Lu, Youpeng; Yue, Wenze; He, Tingting; Shan, Zhuoran
Highlights: Concentric urban form leads to the monocentric urban thermal environment. Intensively concentric urban form has cooling potential on the built-up area. Stability of urban form centrality significantly impacts LST aggregation. Restraining urban sprawl could improve urban thermal environment. Abstract: This paper examines the response of the urban thermal environment to the centrality of urban spatial development. By investigating 27 cases of Chinese megacities, the study quantified the urban form centrality and the spatial pattern of land surface temperature (LST) within built-up areas. Specifically, urban form centrality was measured using the concentric-ring partitioning model, and the landscape metrics and Moran's I were employed to characterize the LST pattern. Then, the correlation between urban form centrality and the LST pattern was examined through ordinary least squares models and global and local bivariate Moran's I. There are three significant findings. First, the urban form centrality dominates the LST centrality along the urban-rural gradient. Second, stably concentric urban forms were inclined toward shape agglomerative and autocorrelated hot areas. Third, enhancing the intensity and reducing the stability of the urban form centrality are preferable to mitigate the urban thermal environment. Fourth, the green space should be embedded around the edge of the built-up area to increase the energy exchange surface. In general, this study has developed a nuanced understanding of the urban form and urban thermal environment and provide climate change adoption strategies for urban planning and public health policies.